Properties of Porous SiC Ceramics Processed by Gelation and Consolidation of Boehmite Coated SiC Suspensions. Issue 4 (2nd October 2017) - Baitalik, Sanchita; Panigrahi, Dipankar; Kayal, Nijhuma
ABSTRACT: SiC powder was dispersed in various concentrations of boehmite sol. The boehmite coated SiC powder was characterized by zeta potential measurement, TEM and FT-IR analyses. Mullite bonded porous SiC ceramics were fabricated by sintering boehmite coated SiC powder compact via a pressureless sintering in air at 1300oC and were characterized by XPS, XRD, SEM analyses. The sintered ceramics have an interconnected open porous network with near uniform pore diameter. Rod shaped mullite crystals were observed in the neck region that bonded the SiC particles together. Effect of boehmite sol concentration on phase composition, microstructure, flexural strength, porosity and pore size distribution was studied. The ceramics synthesized from 30 wt% boehmite sol coated SiC powder contained 26 wt% mullite with ∼30 vol% porosity. GRAPHICAL ABSTRACT: